(untitled) (The Review of Diabetic Studies, 2025)
INTRODUCTION: Diabetes Mellitus is a long-term metabolic condition marked by elevated blood sugar levels, resulting from the body’s insufficient production of insulin or its ineffective use of the insulin it produces. According to the American Diabetes Association, Diabetes Mellitus is divided into two primary types: Type 1 Diabetes Mellitus and Type 2 Diabetes Mellitus. AIM: To assess the effectiveness of Family-Focused Educational Program regarding the Buerger-Allen Exercise to improve lower extremity perfusion in Diabetes Mellitus patients among household members. METHODOLOGY: The research design selected for the study was One Group Pre-Test Post- Test Design under the Quantitative Research Approach. Convienient Sampling Technique was used to select the sample. Sample size were 100 Type 2 Diabetes Mellitus patients. The tools used for study were Socio-demographic variables, Clinical Profile, Family Focused Education Program and Self-Structured Knowledge questionnaire. The collected data were analysed by using descriptive and inferential statistics. RESULTS: The finding of the study showed that Pretest mean score is 11.86±3.327 and Post- test mean score is 20.07±2.583. There has been Significant difference between mean and standard deviation (8.21±0.744) and The maximum 82% participants scored “Good” (16-23) followed by 12% scored “Excellent” (25-30), while only 6 % remained in the “fair” category (8-15). No subjects scored “Poor” (0-7) that showing significant improvement post-interventional knowledge. In term of association with socio-demographic variables, statistically significant association were found between post-knowledge scores that are Age (p=0.015), Religion (p=0.000), Marital status (p=0.000), Occupational status (p=0.000) and Monthly family income (p=0.001). CONCLUSION: The result of the study concluded that practicing Buerger-Allen Exercise improved the lower extremity perfusion among Type 2 Diabetes Mellitus patients.